The effect of educational intervention based on theory of planned behavior and self-regulatory strategies on the social vitality of women employee - Maryam Bahlgerdi; Mohammadreza Miri; Gholamreza Sharifzadeh; Ensiyeh Norozi; Tayebeh Hosseini (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Social vitality is one of the most important social indicators to develop a sense of public satisfaction. The aim of this study was to investigate the effect of educational intervention based on theory of planned behavior (TPB) and self-regulatory strategies on the social vitality of women employee. MATERIALS AND METHODS: In this randomized controlled field trial study, 66 women employees of Birjand University of Medical Sciences (Iran) were selected including intervention (n = 31) and control (n = 35). Data were collected by standard Oxford Happiness Questionnaire and a researcher-made questionnaire based on TPB which its the validity and reliability were confirmed. The educational intervention consisted of 5 sessions based on the constructs of the TPB and self-regulatory strategies which were to the interventional group. Data analysis was performed using the Chi-square, Fisher's exact test, independent t-test, repeated measures ANOVA, and Bonferroni post hoc test at a significance level of <0.05. RESULTS: The mean age of women in the intervention and control group was 37.1 ± 9.3 and 36.2 ± 7.6 years (P = 0.67). Model constructs and happiness scores were homogeneous (P > 0.05) before the intervention, in two group of study, but after attitude (P = 0.016), subjective norm (P = 0.029), perceived behavior control (P = 0.01), intention (P = 0.006), and happiness score (P < 0.001) had a significant increase in the intervention group. In the control group, only a significant difference occurred over time in the happiness rate (P = 0.031). CONCLUSIONS: The results of the present study showed the effectiveness of educational intervention on the social vitality of women employees. Therefore, TPB is recommended to use in interventions to promote social vitality.